The Influence of the Physical Work Environment, Competence, and Work Culture on Motivation and Their Impact on ASN Performance at Regional Office VII of the Palembang State Civil Service Agency - Ramadhan, Rahmad; Yamali, Fakhrul Rozi; Hapsara, Osrita (Dinasti International Journal of Management Science, 2026)
This study aims to analyze the influence of the physical work environment, competence, and work culture on motivation and their impact on the performance of State Civil Apparatus (ASN) at Regional Office VII of the State Civil Service Agency (BKN) Palembang. The background of this study is based on the importance of internal and external organizational factors in improving ASN performance, particularly through the creation of a conducive work environment, improving employee competence, and establishing a positive work culture. The research method used is a quantitative approach with an explanatory research type. The population in this study were all ASN at Regional Office VII of BKN Palembang. Sampling was carried out using a saturated sampling technique, where the entire population was used as a research sample. Data were collected through closed questionnaires and analyzed using path analysis with the help of the SPSS program to determine the direct and indirect relationships between variables. The results of the study indicate that the physical work environment, competence, and work culture have a positive and significant effect on ASN motivation. In addition, motivation has a positive and significant effect on ASN performance, and acts as a mediating variable in the relationship between the variables of the physical work environment, competence, and work culture on ASN performance. These findings indicate that improving the quality of the work environment, strengthening competencies, and implementing a good work culture will encourage higher work motivation, which will ultimately have an impact on improving the performance of ASN in the Palembang Regional Office VII of BKN.